Pengaruh Kepercayaan Diri dan Komunikasi Interpersonal terhadap Kesiapan Mengajar Praktik Pengenalan Lapangan Persekolahan (PLP) pada Mahasiswa FKIP UNS - Farah Ade Nabila; Mientasih Indriayu; Dini Octoria (Departement of Mathematics Education, 2023)
This study aims to determine the effect of self-confidence on teaching readiness for School Field Introduction (PLP) practice to FKIP UNS students, the effect of interpersonal communication on teaching readiness for School Field Introduction (PLP) practice for FKIP UNS students, and the effect of self confidence and interpersonal communication together the same with the readiness to teach the practice of School Field Introduction (PLP) to FKIP UNS students. The research method used is a quantitative descriptive method and data collection techniques using a questionnaire. The sampling technique used probability sampling technique, namely proportionate random sampling with a sample of 331 FKIP UNS students. Validity test using product moment correlation and reliability test using cronbach’s alpha. Data analysis techniques in this study used descriptive statistic analysis, multiple linear regression analysis, t test, and F test. The result of this study indicate that (1) there is a positive and significant effect between self-confident and the readiness to teach the practice of School Field Introduction (PLP) in FKIP UNS students, (2) there is a positive and significant effect between interpersonal communication on the readiness to teach the practice of School Field Introduction (PLP) to FKIP UNS students, (3) there is a positive and significant influence between self-confidence and interpersonal communication together on the readiness to teach the practice of Student Field Introduction (PLP) to FKIP UNS students.